Bromeliad ornamental species: conservation issues and challenges related to commercialization - doi: 10.4025/actascibiolsci.v34i1.7314 - Raquel Rejane Bonato Negrelle; Adilson Anacleto; Darcy Mitchell (Acta Scientiarum: Biological Sciences, 2011)
Bromeliads grow almost exclusively in the New World tropics and subtropics, mainly in South America in the Brazilian Atlantic Forest (ca. 1200 species). Within the last few decades, their beautiful shapes and colors, low maintenance and easy adaptability to small gardens have brought bromeliads into worldwide use as ornamental plants. While the ornamental bromeliad trade could make significant contributions to household economies in rural areas, the trade may represent a significant threat in some of the bromeliad biodiversity hotspot countries such as Brazil, Bolivia and Colombia. This paper presents an overview of production volumes, analysis of the Brazilian bromeliads trade chain – at the state, national and international levels – and recommendations to address development and conservation challenges.